Técnicas, métodos e processos de projeto e construção do sistema construtivo Light Steel Frama - Rondinely Francisco de Lima (2013)
The proposal of this study is to support the development of a Brazilian Technical Standard of design and executive procedures for fabrication and erection of constructive systems structured by the light cold-formed steel profiles, with wall in slim plates, internationally known as Light Steel Frame (LSF). Similar technical standard already exists for constructive systems in plaster board for drywall (ABNT NBR 15758:2009, parts 1, 2 and 3). To compose the set of information it was made the bibliographical revision in publications and national technical standards and foreigners on the subject. Also were considered the knowledge obtained by the author in training courses for design, manufacture and erection of the LSF system - with the construction of a building of social interest housing (HIS) - and technical visits to several constructions and specialized offices. The LSF constructive system was divided into processes, methods and techniques in order to facilitate its understanding and to provide to the professionals the main concepts for the development of projects in a rationalized way, to the light of the good practices of the engineering and of the architecture. Thus, it is waited that with this work, the interested professionals can count with one more reference for the use of the LSF system, and that it is the base of the text for the elaboration of the intended technical standard and be also for the development of new studies and researches on the theme